Thin film pyrolytic carbon electrodes: A new class of carbon electrode for electroanalytical sensing applications - DUESBERG, GEORG; PELTEKIS, NIKOLAOS; MCEVOY, NIALL (My University, 2010)
This communication describes the electrochemical properties of thin pyrolytic carbon (PyC) films created using a reliable, non-catalytic chemical vapour deposition (CVD) process. After deposition, the electron transfer characteristics of the films are optimised using a simple oxygen plasma treatment. The redox probes Ru(NH3)63+/2+, Fe(CN)63?/4? and Fe3+/2+ are employed to demonstrate that the resulting material is endowed with a large electrochemical surface area and outstanding electron transfer properties. Atomic force microscopy (AFM), Raman and X-ray photoelectron spectroscopy (XPS) are used to elucidate the morphology and chemical composition of the electrode surfaces. This material represents a new class of carbon electrode, and its large densities of edge-plane sites and oxygenated functionalities make it an ideal candidate for electrochemical sensor applications.
PUBLISHED
Keywords: Chemistry; Pyrolytic carbon; Nanoscience & Materials